Paciente de sexo femenino de 68 años de edad, que presenta dislipidemia y diabetes mellitus tipo II. - Cabrera Rizzo, Mónica Paola (2020)
The present clinical case study is about a 68-year-old female patient, who presents a pathological history such as obesity, diabetes and is currently diagnosed with atherogenic dyslipidemia. A nutritional assessment was carried out where anthropometric data is evaluated, biochemical, clinical and dietary with the aim of making a comprehensive diagnosis to implement a nutritional treatment with the aim of reducing and controlling the factors that influence the development of other pathologies that affect the nutritional status of the patient. As a result of the anthropometric evaluation, the patient presents a body mass index of 35.74kg/m2 according to the cut-off points of the (Spanish Society of Parenteral and Enteral Nutrition-Spanish Society of Geriatrics and Gerontology, 2007) indicates that he is obese, this reference table was used for older patients, biochemical values such as fasting glucose reveal very high levels resulting in hyperglycemia, glycosylated hemoglobin of 12.7% revealing that she is a poorly controlled patient in her eating habits.